PENGARUH CURRENT RATIO, DEBT TO EQUITY RATIO DAN TOTAL ASSETS TURNOVER TERHADAP RETURN ON ASSETS PADA PT. WIJAYA KARYA (PERSERO) TBK PERIODE 2013-2022 - Amanda Destia Syahputri; Nurismalatri Nurismalatri (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
This research aims to analyze the influence of Current Ratio (CR), Debt to Equity Ratio (DER), and Total Assets Turnover (TATO) on Return on Assets (ROA) at PT Wijaya Karya (Persero) Tbk in 2013-2022. The research method used is a quantitative method. The data source for this research is secondary data in the form of annual financial reports published for the 2013-2022 period. The analytical methods used are descriptive statistical analysis tests, classical assumption tests, multiple linear regression, t tests and F tests, as well as the coefficient of determination. The results of this research show that partially the Current Ratio has no effect on Return on Assets with a t-statistic value of 0.991283 which is smaller than the t-table of 2.446912 with a Prob value. amounting to 0.3598 greater than 0.05, the Debt to Equity Ratio has no effect on Return on Assets with a t-statistic value of -1.150425 which is smaller than the t-table 2.446912 with a Prob value. amounting to 0.2937 greater than 0.05, Total Assets Turnover has a positive and significant effect on Return on Assets with a t-statistic value of 5.721872 greater than the t-table 2.446912 with a Prob value. 0.0012 is smaller than 0.05. Simultaneously the Current Ratio, Debt to Equity Ratio and Total Assets Turnover have an influence on the Return on Assets of PT Wijaya Karya (Persero) Tbk with a FCount value of 18.79076 which is greater than Ftable 4.76 with a Prob value. of 0.0018 is smaller than 0.05. The R-square coefficient of determination is 0.855, meaning that the contribution of the Current